![image](https://tex.z-dn.net/?f=A6.%5C%5C2%5Ccdot%5Cleft%28%5Cfrac19%5Cright%29%5Ex%3D54%5Ccdot%5Cleft%28%5Cfrac13%5Cright%29%5Ex%5C%5C%5Cleft%28%5Cfrac19%5Cright%29%5Ex%3D27%5Ccdot%5Cleft%28%5Cfrac13%5Cright%29%5Ex%5C%5C%5Cleft%28%5Cfrac13%5Cright%29%5E%7B2x%7D-27%5Ccdot%5Cleft%28%5Cfrac13%5Cright%29%5Ex%3D0%5C%5C%5Cleft%28%5Cfrac13%5Cright%29%5Ex%3Dt%2C%5C%3B%5Cleft%28%5Cfrac13%5Cright%29%5E%7B2x%7D%3Dt%5E2%2C%5C%3Bt%3E0%5C%5Ct%5E2-27t%3D0%5C%5Ct%28t-27%29%3D0%5C%5Ct_1%3D0%5C%3B-%5C%3BHe%5C%3Bnogx.%5C%5Ct_2%3D27%5C%5C%5Cleft%28%5Cfrac13%5Cright%29%5Ex%3D27%5C%5C%5Cleft%28%5Cfrac13%5Cright%29%5Ex%3D%5Cleft%28%5Cfrac13%5Cright%29%5E%7B-3%7D%5C%5Cx%3D-3%5C%5COTBET%3A%5C%3B3%29%5C%3B%28-%5Cinfty%3B%5C%3B0%5D)
0\\t^2-27t=0\\t(t-27)=0\\t_1=0\;-\;He\;nogx.\\t_2=27\\\left(\frac13\right)^x=27\\\left(\frac13\right)^x=\left(\frac13\right)^{-3}\\x=-3\\OTBET:\;3)\;(-\infty;\;0]" alt="A6.\\2\cdot\left(\frac19\right)^x=54\cdot\left(\frac13\right)^x\\\left(\frac19\right)^x=27\cdot\left(\frac13\right)^x\\\left(\frac13\right)^{2x}-27\cdot\left(\frac13\right)^x=0\\\left(\frac13\right)^x=t,\;\left(\frac13\right)^{2x}=t^2,\;t>0\\t^2-27t=0\\t(t-27)=0\\t_1=0\;-\;He\;nogx.\\t_2=27\\\left(\frac13\right)^x=27\\\left(\frac13\right)^x=\left(\frac13\right)^{-3}\\x=-3\\OTBET:\;3)\;(-\infty;\;0]" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=B1.%5C%5C%5Csqrt%7Bx-1%2C5%7D%5Ccdot%5Cleft%282%5Ex%2B8%5Ccdot2%5E%7B-x%7D-6%5Cright%29%3D0%5C%5CO.D.3.%3A%5C%3Bx-1%2C5%5Cgeq0%5CRightarrow+x%5Cgeq1%2C5%5C%5C1%29%5C%3B%5Csqrt%7Bx-1%2C5%7D%3D0%5CRightarrow+x_1%3D1%2C5%5C%5C2%29%5C%3B2%5Ex%2B8%5Ccdot2%5E%7B-x%7D-6%3D0%5C%5C2%5Ex%2B%5Cfrac8%7B2%5Ex%7D-6%3D0%5C%5C2%5Ex%3Dt%2C%5C%3Bt%3E0%5C%5Ct%2B%5Cfrac8t-6%3D0%5C%5C%5Cfrac%7Bt%5E2-6t%2B8%7Dt%3D0%5C%5Ct%5E2-6t%2B8%3D0%5C%5CD%3D36-4%5Ccdot8%3D36-32%3D4%5C%5Ct_%7B1%2C2%7D%3D%5Cfrac%7B6%5Cpm2%7D2%5C%5Ct_1%3D2%2C%5C%3Bt_2%3D4%5C%5C2%5Ex%3D2%5CRightarrow+x_2%3D1%5C%3BHe%5C%3Bnogx.%5C%3Bno%5C%3BO.D.3.%5C%5C2%5Ex%3D4%5CRightarrow+x_3%3D2%5C%5C%5C%5Cx_1%2Bx_3%3D1%2C5%2B2%3D3%2C5)
0\\t+\frac8t-6=0\\\frac{t^2-6t+8}t=0\\t^2-6t+8=0\\D=36-4\cdot8=36-32=4\\t_{1,2}=\frac{6\pm2}2\\t_1=2,\;t_2=4\\2^x=2\Rightarrow x_2=1\;He\;nogx.\;no\;O.D.3.\\2^x=4\Rightarrow x_3=2\\\\x_1+x_3=1,5+2=3,5" alt="B1.\\\sqrt{x-1,5}\cdot\left(2^x+8\cdot2^{-x}-6\right)=0\\O.D.3.:\;x-1,5\geq0\Rightarrow x\geq1,5\\1)\;\sqrt{x-1,5}=0\Rightarrow x_1=1,5\\2)\;2^x+8\cdot2^{-x}-6=0\\2^x+\frac8{2^x}-6=0\\2^x=t,\;t>0\\t+\frac8t-6=0\\\frac{t^2-6t+8}t=0\\t^2-6t+8=0\\D=36-4\cdot8=36-32=4\\t_{1,2}=\frac{6\pm2}2\\t_1=2,\;t_2=4\\2^x=2\Rightarrow x_2=1\;He\;nogx.\;no\;O.D.3.\\2^x=4\Rightarrow x_3=2\\\\x_1+x_3=1,5+2=3,5" align="absmiddle" class="latex-formula">